2016
DOI: 10.1186/s13068-016-0445-x
|View full text |Cite
|
Sign up to set email alerts
|

Consolidated bioprocessing of Populus using Clostridium (Ruminiclostridium) thermocellum: a case study on the impact of lignin composition and structure

Abstract: Background Higher ratios of syringyl-to-guaiacyl (S/G) lignin components of Populus were shown to improve sugar release by enzymatic hydrolysis using commercial blends. Cellulolytic microbes are often robust biomass hydrolyzers and may offer cost advantages; however, it is unknown whether their activity can also be significantly influenced by the ratio of different monolignol types in Populus biomass. Hydrolysis and fermentation of autoclaved, but otherwise not pretreated Populus trichocarpa by Clostridium the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
64
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 47 publications
18
64
1
1
Order By: Relevance
“…The trends for acetic acid and ethanol were similar until 120-h postinoculation. Although the concentration of acetic acid was found to be 0.6 g/l after 139 h of microbial growth, ethanol stopped accumulating after 120 h. Acetic acid increased from ≤0.075 g/l at time zero to ~0.7 g/l after 187 h, and it continued to slowly accumulate throughout the experiment, consistent with other studies [27]. The time points of 19 and 43 h represent early and late exponential growth phase, respectively, and the cultures began to transition into stationary phase around 100-h postinoculation.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The trends for acetic acid and ethanol were similar until 120-h postinoculation. Although the concentration of acetic acid was found to be 0.6 g/l after 139 h of microbial growth, ethanol stopped accumulating after 120 h. Acetic acid increased from ≤0.075 g/l at time zero to ~0.7 g/l after 187 h, and it continued to slowly accumulate throughout the experiment, consistent with other studies [27]. The time points of 19 and 43 h represent early and late exponential growth phase, respectively, and the cultures began to transition into stationary phase around 100-h postinoculation.…”
Section: Resultssupporting
confidence: 91%
“…Thus, both are indicative of metabolic activity and cell growth. However, acetic acid can also be generated through deacetylation of hemicelluloses, [27] and thus the relative contributions from the pretreated biomass or bacteria cannot be easily differentiated in this study. Ethanol production, however, is exclusive to C. thermocellum and therefore a more specific indicator of microbial growth, especially given the complex culture conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The measured A O adsorption was significantly smaller on unpretreated biomass than the pretreated biomass reported in [22] likely due to the cell wall matrix in pretreated biomass being disrupted by pretreatment leading to increased cellulose exposure. Significantly lower DO adsorption was also reported on unpretreated poplar [24, 25]. In addition, the switchgrass adsorbed more orange than blue and the O/B ratio was higher in the transgenic (1.35 and 1.09) relative to the control (1.02 and 0.98) group.…”
Section: Resultsmentioning
confidence: 65%
“…1 filter paper 317.15.3ND20[26]CS8Milled Whatman No. 1 filter paper 318.07.2ND20[26]JN4Avicel 56.27.61360[59]YSAvicel 2036.012.0ND[27]ATCC 35609MN300 831.222.5ND120[60]JW20Avicel 1025.413.09.416[28]YM4Avicel 1044.726.520.496[61]BC1Whatman No. 1 filter paper 10102ND144[40]DBT-IOC-C19Avicel 1032.5518.675.1496This study

ND not detected, metabolite yield reported as g L −1 converted to millimolar using a molecular weight of 46.07 g mol −1 for ethanol, 60.05 g mol −1 for acetate, and 90.08 g mol −1 for lactate

…”
Section: Resultsmentioning
confidence: 99%